The Impact of Intellectual trends on the nature of the Economic Structure of Iraq - العبيدي عبد الجبار محمود; خلف اسماء طه (Journal of Economics and Administrative Sciences, 2012)
The Impact of Intellectual trends on the nature of the Economic Structure of Iraq